Bridging the gap: metabolic and endocrine care of patients during transition. Issue 6 (November 2016) - Hokken-Koelega, Anita; van der Lely, Aart-Jan; Hauffa, Berthold; Häusler, Gabriele; Johannsson, Gudmundur; Maghnie, Mohamad; Argente, Jesús; DeSchepper, Jean; Gleeson, Helena; Gregory, John W; Höybye, Charlotte; Keleştimur, Fahrettin; et al.
Abstract : Objective: Seamless transition of endocrine patients from the paediatric to adult setting is still suboptimal, especially in patients with complex disorders, i.e., small for gestational age, Turner or Prader–Willi syndromes; Childhood Cancer Survivors, and those with childhood-onset growth hormone deficiency. Methods: An expert panel meeting comprised of European paediatric and adult endocrinologists was convened to explore the current gaps in managing the healthcare of patients with endocrine diseases during transition from paediatric to adult care settings. Results: While a consensus was reached that a team approach is best, discussions revealed that a 'one size fits all' model for transition is largely unsuccessful in these patients. They need more tailored care during adolescence to prevent complications like failure to achieve target adult height, reduced bone mineral density, morbid obesity, metabolic perturbations (obesity and body composition), inappropriate/inadequate puberty, compromised fertility, diminished quality of life and failure to adapt to the demands of adult life. Sometimes it is difficult for young people to detach emotionally from their paediatric endocrinologist and/or the abrupt change from an environment of parental responsibility to one of autonomy. Discussions about impending transition and healthcare autonomy should begin in early adolescence and continue throughout young adulthood to ensure seamless continuum of care and optimal treatment outcomes. Conclusions: Even amongst a group of healthcare professionals with a great interest in improving transition services for patients with endocrine diseases, there is still much work to be done to improve the quality of healthcare for transition patients.